The Effects of Emotional Intelligence on Teachers’ Classroom Performance: A Case of Primary Schools in Southeast Region of Botswana - Tshireletso Philemon Kgosiemang; Samuel Dumazi Khoza (Research in Social Sciences and Technology, 2022)
The purpose of the study was to examine the effects of emotional intelligence (EI) on teachers’ performance in Southeast Region primary schools in Botswana. The research methodology applied was mixed methods. The target group consisted of 300 teachers from 16 primary schools in Botswana's Southeast Region. The participants were chosen using a simple random sampling procedure. Seventy (70) out of 300 teachers comprising both males and females with years of work experience ranging from less than 2 to more than 10 were used as the sample in the study. The 9-layered model of the EI pyramid was used as the theoretical framework for the study. The pragmatism paradigm was used to blend qualitative and quantitative research approaches to arrive at trustworthy conclusions about the effects of EI on teacher performance in primary schools in Botswana's Southeast Region. The findings of the study revealed that primary school teachers in the Southeast Region of Botswana require EI skills to enhance their performance, improve their attitudes towards their instructional practices, and apply appropriate ways of assisting and encouraging struggling learners and colleagues. The findings also indicated a link between teachers' EI and academic performance.